MANAJEMEN KEPALA SEKOLAH DALAM PEMBENTUKAN KARAKTER RELIGIUS, DISIPLIN, DAN KREATIF PADA PESERTA DIDIK SMK FULL DAY SUNAN AMPEL BANGOREJO BANYUWANGI - Moh. Harun Al Rosid Rosid; Imam Ghozali Alfaruq (Institut Agama Islam Darussalam Blokagung, 2023)
Management must be based on the representation of leaders to carry it out in developing character education, especially religious, disciplined and creative. Leaders are only a small number of individuals who are considered to have the right things to serve and can be called leaders. Naturally, the individual has the mental, emotional, and physical capacity to think and act as a leader. The objectives of this research are to 1). understand the principal's management in forming religious, disciplined and creative character in Sunan Ampel Full Day Vocational School students. 2). To find out the factors that influence the principal's management in forming religious, disciplined and creative character in Sunan Ampel Full Day Vocational School students. The approach in this research is qualitative with a qualitative descriptive research type. Data collection techniques using interviews, observation and documentation. Data validity by triangulating sources, methods and investigations as well as data analysis using the interaction of Miles and Hubberman's 3 models including: 1. data reduction, 2. data presentation, 3. drawing conclusions. The results of this research show that: (1) The management of the principal in forming religious, disciplined and creative character at Full Day Vocational School Sunan Ampel Bangorejo Banyuwangi, the strategy used in religious character uses habituation, and examples are given from the principal with the teacher council, then the participants learn to follow it. (2) Supporting factors for school principal management in the formation of religious, disciplined and creative character are control from the teacher council, as well as support from the community. The inhibiting factor for the school is that it requires extra energy to deal with students who have different characters and dispositions.